A Development Strategy for the Revival of Tourist Hotspots following the COVID-19 Pandemic - Bautista, Hugo; Valeeva, Gulnara; Danilevich, Victoria; Zinovyeva, Alfiya (International Journal of Criminology and Sociology, 2022)
The ongoing Covid-19 crisis has hit many sectors and industries in the hardest possible way. Travel and tourism-related activities have not been an exception. We contend that a systemic approach can be developed and implemented in order to trace and certify individuals who do not present an epidemiological risk to other people, and also to manage their close interaction. This could lead to the certification of a large proportion of the population—millions worldwide—as not representing a risk of infection to others. It can justify the implementation of a system that can speed up the reactivation of several economic sectors and industries, protecting jobs and accelerating economic recovery in many countries. People who have been ill with Covid-19 have acquired the corresponding antibodies and, therefore, have immunity to the disease, they could travel freely, thereby helping to reactivate the economy. We will explain in this paper how a number of high-tech tools can be implemented as a crowd control system to identify those who do not represent a risk to others, either because they have acquired immunity or because they can be regarded as not carriers of a communicable disease. We devise a method based on the use of a 3D-diagram that shows the existence of an inverse relation between the number of tests performed and the number of individuals that have contracted the disease. The results of the study suggest that the implementation of a new epidemiological tourist strategy in Cuba can help to reactivate tourist activities in the country while avoiding the creation of new hotbeds of infection for Covid-19.